Developing countries and the industry 4.0 movement: Research mapping for practical insights - Hammad, Muhammad Yahya; Syed Radzi, Rahamaddulla; Sorooshian, Shahryar; Puteri Fadzline, Muhamad Tamyez; Muhammad Ashraf, Fauzi (CRIBFB, 2025)
This paper investigates the adoption of Industry 4.0 in developing countries, emphasizing the unique challenges these economies face compared to advanced nations. Despite the global spread of digital technologies such as automation, big data analytics, and the Internet of Things (IoT), adoption in resource-constrained contexts remains limited due to inadequate infrastructure, financial restrictions, skill gaps, and organizational resistance. To address these issues, the study employs a bibliometric methodology, analyzing 398 journal articles indexed in Web of Science through co-word and bibliographic coupling techniques. This approach enables the mapping of dominant themes, influential research clusters, and key gaps in the literature. The results highlight five thematic areas: global technological developments, sustainability integration, adoption barriers, implementation practices, and strategies for overcoming obstacles. Findings indicate that while challenges are considerable, Industry 4.0 can enhance productivity, stimulate Innovation, and support sustainability by strengthening supply chains and promoting efficient resource use. The study also reveals that transformative benefits can only be realized when supportive policies, international collaboration, private-sector participation, and workforce development are followed in a coordinated manner. The research contributes to theory by linking Industry 4.0 adoption to sustainability frameworks such as the Circular Economy and the Sustainable Development Goals. It also offers practical guidance for policymakers, SMEs, and managers on designing context-sensitive strategies tailored to developing economies. By providing a structured overview of challenges and opportunities, the study lays a foundation for future empirical research and offers actionable insights for advancing sustainable industrial transformation.